POLA DAN EVALUASI PENGGUNAAN LAHAN DI SEMPADAN SUNGAI CINANGKA, SUB DAERAH ALIRAN SUNGAI CIMANUK HULU (Pattern and evaluation of land use in Cinangka Buffer Zone, Upper Cimanuk Sub Watershed) - Ary Widiyanto; Aditya Hani (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2018)
ABSTRACTIn general, watershed problems are caused by two factors namely natural factors such as rainfall, slopes and soil types and human factors such as policy and socio-economic factors. This study aims to evaluate the existing land use compared to Regional Spatial Planning of Garut in the buffer zone of Cinangka River, which is part of the Upper Cimanuk sub watershed. This research is expected to contribute to the watershed management knowledge and offer an alternative model for watershed management based on dynamic socio-economic conditions. Primary data collection was conducted through field surveys and interviews to the selected farmers whose land were in the selected areas. The interviews were to find out the reasons for planting the chosen crops. An observation plot of 50 meters for each river boundary as long as 1 km, were made to evaluate the land use. Therefore, total area of observation was 100.000 m2 or 10 hectare (ha). The study area is dominated by monoculture farming, which is 62% of the total area. Other land uses include bare land and shrubs (13.2%), agroforestry (12.3%), forest trees (trees & MPTS) (11.6%), and other types of land use (1%). The use of monoculture agriculture in this area is not accordance to the Regional Spatial Plans (RTRW) of Garut Regency in 2011-2031, which allocates the area of Cinangka sub watershed as community forest cultivation.Keywords: agroforestry; land use; monoculture farm; Cinangka River ABSTRAKPenyebab utama permasalahan Daerah Aliran Sungai (DAS) secara umum dapat dikelompokkan menjadi dua faktor yakni faktor alam seperti curah hujan, kelerengan dan jenis tanah dan faktor manusia seperti faktor kebijakan dan sosial ekonomi. Penelitian ini bertujuan untuk mengevaluasi penggunaan lahan terhadap kesesuaian RTRW Kabupaten Garut di sempadan Sungai Cinangka, yang masuk dalam Sub DAS Cimanuk Hulu. Hasil penelitian diharapkan dapat meningkatkan khasanah dan menjadi masukan perbaikan bagi ilmu pengelolaan DAS sekaligus memberi alternatif model pengelolaan DAS berdasarkan kondisi sosial ekonomi yang dinamis. Pengumpulan data primer dilakukan dengan survei lapangan dan wawancara dilakukan dengan petani yang lahannya masuk dalam areal pengukuran, untuk mengetahui alasan mereka menanam jenis tanaman tertentu. Untuk mengevaluasi penggunaan lahan di sempadan Sungai Cinangka dilakukan dengan membuat plot sepanjang 1 km, dan masing-masing 50 m tepi kanan dan kiri sungai sehingga luas total area pengamatan adalah 100.000 m2 atau 10 hektar (ha). Pertanian monokultur mendominasi pola penggunaan lahan di sempadan Sungai Cinangka, Sub DAS Cimanuk Hulu dengan jumlah penggunaan lahan sekitar 62% dari total area. Penggunaan lahan lainnya meliputi lahan terbuka dan semak (13,2%), agroforestri (12,3%), tanaman kehutanan (pohon & MPTS) (11,6%), dan jenis penggunaan lain-lain (1%). Penggunaan lahan pertanian monokultur di daerah ini tidak sesuai dengan Rencana Tata Ruang Wilayah (RTRW) Kabupaten Garut Tahun 2011-2031 yang menetapkan kawasan Sub DAS Cinangka dalam kawasan budidaya hutan rakyat.Kata kunci: agroforestri; penggunaan lahan; pertanian monokultur; Sungai Cinangka